The Problems Faced by the Teachers and the Students in Teaching and Learning ESP Reading Skill at Thanh Hoa University of Culture, Sports and Tourism - Hong Hanh, Nguyen Thi (International Journal of Humanities and Education Development (IJHED), 2023)
This paper was conducted to see the problems faced by the teacher and the students in teaching and learning ESP reading skill at Thanh Hoa University of Culture, Sports and Tourism. So as to gather more believable data, the qualitative method including the author's personal observation, the discussion and interview with the students and the colleagues. The collected data revealed the teachers and students’ difficulties in teaching and learning ESP reading and their causes. Based on the author’s experience, the discussion and interview with the colleagues and students, the researcher gave some possible solutions to improve the quality of teaching and learning ESP reading at school.